Acute monocyte pro inflammatory response predicts higher positive to negative acute phase reactants ratio and severe hemostatic derangement in dengue fever - Choudhuri, Subhadip; Chowdhury, Imran Hussain; Saha, Avijit; Mitra, Bhaskar; Dastidar, Rinini; Roy, Pijush Kanti (Cytokine (Philadelphia, Pa.), 2021)
[Display omitted] •Monocyte proinflammatory response is associated with plasma positive to negative acute phase reactants ratio and predicts hemostatic derangement mediated severe disease outcome in dengue infection.•We evaluated an important interplay of monocyte expressed cytokines and plasma positive acute phase reactants (APRs) in the immunopathogenesis of dengue infection.•Secondary dengue infection is more critical and induces monocyte proinflammatory cytokine expression that in turn modulates plasma positive to negative acute phase response.•Our present findings of altered positive to negative APRs ratio may provide us with a prospective tool for disease severity risk assessment among the subjects who acquired secondary dengue infection. The present study was intended to investigate whether monocyte immune activation shapes plasma positive to negative acute phase reactants (APRs) ratio and predicts disease severity in dengue infection. Serum level of ferritin, ceruloplasmin and transferrin was measured by means of electrochemiluminescence and immunoturbidimetry, respectively. Gene expression and plasma level for TNF-α, IL-6 and IL1-β was measured by means of RT-qPCR and ELISA. A significant increased serum ferritin to transferrin [6.6 (3–11.7) vs 3.4 (1.9–6.1)] and ceruloplasmin to transferrin ratio [0.48 (0.21–0.87) vs 0.22 (0.13–0.43)] has been detected among the subjects with secondary dengue infection (SDENI) compared to primarily infected (PDENI) subjects (P < 0.001). Significant increased expression for CD14+ monocyte TNF-α, IL-6 and IL-1β has been detected in SDENI patients (vs PDENI and control, P < 0.001). Plasma ferritin to transferrin ratio was found in a significant association with high level of plasma TNF-α [ρ = 0.6522, 95% CI (0.4714–0.7805)], IL-6 [ρ = 0.6181, 95% CI (0.4257–0.7571)] and IL- 1β [ρ = 0.4119, 95% CI (0.1689–0.6077)] level among SDENI patients at 5th day time point after progression of the disease, with significantly low platelet [P < 0.001] and prolonging prothrombin time [P < 0.001] compared to control and PDENI subjects, respectively. Acute proinflammatory cytokine response is significantly associated with increased positive to negative APRs ratio in SDENI patients, which predicts intense immune activation, and renders SDENI patients extremely susceptible to hemostatic derangement.